A numerical study of the impact of wet clutch drag torque on the performance of two-speed electric vehicles. Issue 2 (2016) - Zhou, Xingxing; Walker, Paul D.; Zhang, Nong
In order to study the economy performance of a two-speed electric vehicle (EV) equipped with a wet dual clutch transmission (DCT), this paper presents a theoretical analysis of drag torque in wet clutches, and investigates the relationship between drag torque, transmission gear ratios, and their optimisation. As such, the application of drag torque effects in gear ratio optimisation is conducted. Through this paper mathematic models for a two-speed EV is presented and a procedure to obtain the reasonable optimal gear ratio pairs and corresponding shift schedule for a two-speed EV is described in detail, with consideration of wet clutch drag torque. Through simulation and parametric analysis using different test driving cycles, including constant speed, NEDC and UDDS, the effects of drag torque is studied in gear ratio selection and EV efficiency and economy, with result demonstrating a significant influence on overall vehicle performance, and degradation of drivetrain efficiency.